(untitled) (Fiep Bulletin - online, 2012)
The study addressed the theme "Adapted Physical Education", in order to check their progress and as part of society. The study was based on qualitative literature, where it was used to study various articles, books and other materials, and then find answers to questions that motivated this study. Upon completion of the readings, it was found that there was a great evolution of Adapted Physical Education, especially from the twentieth century to the present day. As a matter of fact, it was stopped working only with individuals so called "normal", and activities were developed in which the idea of students as a whole was included. Currently there are several laws that support people with special needs such as PCNs and LDB, what makes today’s schools have an obligation of including these people in the mainstream education, a current fact that did not occur before.